The Level of Community Knowledge and Behavior Regarding Drug Destruction in the Community Health Center in 2023 - Puspasari, Heny; Suryaningrat, Dani; Silfia, Sella (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR), 2025)
People often throw drugs directly into the trash without separating the drugs first. Based on research conducted in the community of Pucang Sewu Village, Surabaya showed that 57.9% of 140 respondents did not dispose of drugs properly. This study aims to determine the level of knowledge and behavior of the community related to drug destruction in the community at Sungai Raya Dalam. This research included descriptive conducted on the community at Sungai Raya Dalam. The sampling method used is Accidental Sampling. The instrument used is a questionnaire. This research will be conducted from April–May 2024. The results of the research data showed the level of knowledge of respondents about drug destruction both as many as 64 people with a percentage of 64%, enough 33 people with a percentage of 33%, and less than 3 people with a percentage of 3% and positive behavior about drug destruction 93 people with a percentage of 93% and negative behavior of 7 people with a percentage of 7%. Based on the results of the research conducted, it can be concluded that the majority of people in the community in the health community at Sungai Raya Dalam have good knowledge of drug destruction and have positive behavior in drug destruction.